An Information Systems Study on Resins, Incorporated Repair and Maintenance System - Agnir, Pocholo; Domingo, Jake; Hosaka, Harry; Pugeda, Mael; Rapes, Jerry; Villanueva, Joji (College of Engineering, 1987)
RESINS, Incorporated is one of the leading chemical manufacturers of the Philippines. One of its primary objectives is to continue their reliable services in terms of punctual delivery. Its fleet of delivery vehicles is properly maintained by the Repair and Maintenance Department. There are two main functions performed by the Repair and Maintenance Department, namely: Preventive Maintenance. The Repair and Maintenance Department performs a thorough check-up of the parts and actual performance of each delivery vehicle. The foremost desire of this function is to prolong equipment life through improved conditioning. Actual Repair. The Repair and Maintenance Department conducts actual repair on major and minor breakdowns or damages experienced by the delivery vehicles. They try to accomplish their work as fast as possible, to ensure prompt delivery.